2019
DOI: 10.1038/s41598-019-46139-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Composite LED Light on Root Growth and Antioxidant Capacity of Cunninghamia lanceolata Tissue Culture Seedlings

Abstract: We used the 12 th generation of the Cunninghamia (C.) lanceolata tissue culture seedlings, and white light emitting diode (LED) light as control (CK). We applied five composite LED light treatments, red-blue 4:1, 8:1 (4R1B and 8R1B), red-blue-purple 8:1:1 (8R1B1P), and red-blue-purple-green 6:1:1:1, 8:1:1:1 (6R1B1P1G and 8R1B1P1G), to study the effects of light quality on root growth characteristics and antioxidant capacity of C. lanceolata t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…The plant materials were formally identified by Lecturer Rongyan Deng and deposited in the laboratory of College of Forestry at Guangxi University. The plantlets were pretreated as described by Xu et al [48]. Subsequently, 540 healthy unrooted shoots with consistent growth (approximately 1.5 ± 0.2 cm height) were applied to further LED experiments.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The plant materials were formally identified by Lecturer Rongyan Deng and deposited in the laboratory of College of Forestry at Guangxi University. The plantlets were pretreated as described by Xu et al [48]. Subsequently, 540 healthy unrooted shoots with consistent growth (approximately 1.5 ± 0.2 cm height) were applied to further LED experiments.…”
Section: Plant Materialsmentioning
confidence: 99%
“…For example, significantly improved biomass yield, increased shoot regeneration, and improved adaptability and survival rate of regenerated plants have been reported [ 30 , 31 , 32 , 33 ]. Improved secondary metabolite accumulation and in vitro root growth have been reported by Xu et al [ 34 ] in Cunninghamia lanceolata and Nadeem et al [ 35 ] in Ocimum basilicum under LED irradiation. Plant growth, development, and metabolite production are strongly affected by the light spectrum of the LEDs.…”
Section: Introductionmentioning
confidence: 79%
“…LED irradiation of various cultured plants also increased in vitro adventitious root induction. For example, the adventitious root-promoting effects of LED irradiation were observed in strawberries [ 122 ], chrysanthemum [ 123 ], chestnuts [ 124 ], Oncidium [ 113 ], and C. lanceolata [ 34 ]. The effects of spectral differences in light quality on somatic embryo formation have been reported in Peucedanum japonium [ 125 ], Coffea canephora [ 126 ], Pinus densiflora [ 127 ], Pinus taeda , and Pinus elliottii [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Promotion of in vitro root induction and development by red LED treatments has been reported for various plant species, including Tripterospermum japonicum (Moon et al, 2006), grape (Poudel et al, 2008), banana (Wilken et al, 2014), R. glutinosa (Manivannan et al, 2015), and Cunninghamia lanceolata (Xu et al, 2019). The interaction between light quality and cytokinin content in media on multiplication and growth was evaluated during in vitro culture of Myrtus communis L. The results indicated that the highest number of shoots was obtained under red LEDs with the lowest concentration of cytokinin in the media (Cio c et al, 2018).…”
Section: Cytokinin Zmentioning
confidence: 97%